DEHUMIDIFIER DRYING OF SEAGRASS SIMPLICIA AT LOW TEMPERATURE FOR ANTIOXIDANT AND PHENOLIC PRESERVATION - Bambang Susilo; Mukhammad Abdul Jabbar Filayati; Mochamad Bagus Hermanto; Retno Damayanti; Adamas Akbar Yurisdanto; Abd. Rohim (Jurnal Teknologi Pertanian, 2023)
Syringodium isoetifollium is seagrass a marine plant which is mostly found in Indonesian sea waters. Phenol is a kind of sensitive heat compound which will damage at high temperatures. This research aimed to study the effect of temperature using a dehumidified drying machine on the quantity of phenol content and testing of this antioxidant activity and the evaluation of drying characteristics of seagrasses such as decrease of moisture content, the distribution of temperature drying relative humidity, and energy consumption. In this research, the independent variaable were tempeartures (30 °C, 40 °C, and 50 °C) and the independent variable were the content of phenol and antioxidant activity of the seagrasses. The phenol content of each extract was measured with a microplate reader using a Follin-Ciocalteu reagent. The antioxidant activity was measured with the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The result showed that the highest content of phenolic compounds (80.42766 ± 0.409a) and antioxidant activity (88.4185 ± 32.0709a) was found in the dehumidified dryer at a temperature of 40 °C. There were significant differences between temperatures of 30 °C and 50 °C. Dehumidifier drying at 30 °C, 40 °C, and 50 °C required 13 hours, 12 hours, and 7.5 hours to reach the final moisture content of seagrass 18-20% from the initial moisture content of 89.4% ± 0.04% (wb). The total phenol content and antioxidant activity with a temperature treatment of 40 °C dehumidifier drying machine showed the best results compared to temperatures of 30 °C, 50 °C, and oven at 40 °C. Based on the same temperature treatment, dehumidifier drying requires a faster time (12 hours) than oven drying (17 hours). The appropriate temperature and time of drying can produce the optimal total phenol and antioxidant activity.